Adaptive (Cr, Al)N+Mo:Sg Coating for Highly‐Stressed Contacts under Dry Rolling‐Sliding Conditions. (October 2022) - Bobzin, K.; Kalscheuer, C.; Thiex, M.; Stahl, K.; Lohner, T.; Maier, E.; Yilmaz, M.
Abstract: Highly-stressed rolling-sliding contacts under fluid-free lubrication as found in ultralightweight gear applications require effective friction and wear reduction. Promising approaches are PVD deposited Mo:S-modified nitride coatings (Cr, Al)N+Mo:Sg and Zr modified diamond-like-carbon coatings ZrCg that provide transfer film-based self-lubrication. In this study, the self-lubrication mechanism of both systems is tribologically tested on a twin-disk tribometer and physiochemically analyzed by secondary electron microscopy and Raman spectroscopy. MoS2 lacquer provides the reference. Results reveal lowest friction and stable self-lubrication through in-situ MoS2 - and Mox Oy -rich transfer films from (Cr, Al)N+Mo:Sg on the steel counter surfaces. High pressures and pure rolling conditions favor the transfer film formation. Highlights: Low friction and stable operating conditions through (Cr, Al)N+Mo:Sg . Transfer film from (Cr, Al)N+Mo:Sg is composed of molybdenum disulfide and oxide. Transfer film enables chemical adaption to tribological conditions.